Protein Kinase CK2 in Cancer Energetics - Silva-Pavez, Eduardo; Tapia, Julio C. (Frontiers in Oncology, 2020)
Protein kinase CK2 (formerly known as casein kinase 2) is abnormally elevated in many cancers. This may increase tumor aggressiveness through CK2-dependent phosphorylation of key proteins in several signaling pathways. In this work, we have compiled evidence from the literature to suggest that CK2 also modulates a metabolic switch characteristic of cancer cells that enhances resistance to death, due to either drugs or to a microenvironment deficient in oxygen or nutrients. Concurrently, CK2 may help to preserve mitochondrial activity in a PTEN-dependent manner. PTEN, widely recognized as a tumor suppressor, is another CK2 substrate in the PI3K/Akt signaling pathway that promotes cancer viability and aerobic glycolysis. Given that CK2 can regulate Akt as well as two of its main effectors, namely mTORC1 and b-catenin, we comprehensively describe how CK2 may modulate cancer energetics by regulating expression of key targets and downstream processes, such as HIF-1 and autophagy, respectively. Thus, the specific inhibition of CK2 may lead to a catastrophic death of cancer cells, which could become a feasible therapeutic strategy to beat this devastating disease. In fact, ATP-competitive inhibitors, synthetic peptides and antisense oligonucleotides have been designed as CK2 inhibitors, some of them used in preclinical models of cancer, of which TBB and silmitasertib are widely known. We will finish by discussing a hypothetical scenario in which cancer cells are “addicted” to CK2; i.e., in which many proteins that regulate signaling pathways and metabolism-linked processes are highly dependent on this kinase.